Minimally invasive organ‐preserving approaches in the management of mesh erosion after laparoscopic ventral mesh rectopexy. (15th September 2020) - Ratnatunga, K.; Singh, S.; Bolckmans, R.; Goodbrand, S.; Gorissen, K.; Jones, O.; Lindsey, I.; Cunningham, C.
Abstract: Aim: This is a systematic approach for minimally invasive methods in the management of mesh erosion after laparoscopic ventral mesh rectopexy. Methods: All patients managed with organ‐preserving techniques for mesh erosion were identified from a prospective database and clinical records were reviewed. Each patient was contacted via telephone and a structured questionnaire was applied. A Likert score was used to assess patient symptoms and overall satisfaction with management. One or more of the following techniques were used: (i) transanal or transvaginal trimming/excision of exposed mesh and sutures, with or without using transanal endoscopic micro surgery or transanal minimally invasive surgery; (ii) laparoscopic pelvic assessment and detachment of mesh from the sacral promontory. Results: Eleven patients were managed for mesh erosion with organ‐preserving techniques. All were women with a median age of 60 years [interquartile range (IQR) 53.5–68.5]. Vaginal, rectal, perineal erosion and recto‐vaginal fistulation occurred in five, four, one and one patient respectively. Vaginal erosions presented at a median of 51 months (IQR 36–56) after index laparoscopic ventral mesh rectopexy compared to 17.5 months (IQR 14.5–27.25) for the rectal erosions. Median follow‐up time was 24 months (IQR 19–49). Four of the meshes (36%) were removed completely whereas seven (63%) were partially removed. Vaginal erosions required a median of two procedures to achieve resolution as opposed to five for rectal. Out of 11 patients, eight were satisfied with the outcome of their management, whereas two were not and one remained ambivalent. Conclusion: An organ‐sparing minimally invasive approach is feasible in managing mesh erosions but requires multiple procedures and months to complete.